2019
DOI: 10.1080/09638288.2019.1641847
|View full text |Cite
|
Sign up to set email alerts
|

Measures used to assess impact of providing care among informal caregivers of persons with stroke, spinal cord injury, or amputation: a systematic review

Abstract: Purpose: (1) To identify measures used to evaluate the impact of caregiving among caregivers of persons with stroke, spinal cord injury, and amputation; and (2) to systematically evaluate their clinimetric properties reported in validation studies. Materials and methods: Two separate systematic reviews (Embase, PsycINFO, CINAHL, Pubmed/Medline) were conducted. COSMIN guidelines were used to assess clinimetric properties and methodological quality of studies. Results: (1) 154 studies published between 2008 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 299 publications
0
15
0
1
Order By: Relevance
“…Caregiving exposes the informal caregiver to a number of unexpected and stressful situations that require changes in their lifestyles 6,7. Other perspectives point out that not all caregivers develop illnesses or stress exhaustion, suggesting that individuals show variability in responses to changes, that differ from individual to individual and over time 43,44. In this study, caregivers with low levels of stress showed higher levels of mental quality of life over time, thus emphasising the adverse role of continuous stress.…”
Section: Discussionmentioning
confidence: 55%
“…Caregiving exposes the informal caregiver to a number of unexpected and stressful situations that require changes in their lifestyles 6,7. Other perspectives point out that not all caregivers develop illnesses or stress exhaustion, suggesting that individuals show variability in responses to changes, that differ from individual to individual and over time 43,44. In this study, caregivers with low levels of stress showed higher levels of mental quality of life over time, thus emphasising the adverse role of continuous stress.…”
Section: Discussionmentioning
confidence: 55%
“…Notes. a lower score better; b higher score better; * rated by Scholten et al, 2019; †rated by the COSMIN team. Abbreviations: SDstandard deviation; IQRinterquartile range.…”
Section: Discussionmentioning
confidence: 99%
“…Psychometric properties are most frequently evaluated according to the measure's validity and reliability. To date, a few studies have assessed the psychometric properties of "burden" or "quality of life" measures among care partners of people with neurodegenerative diseases (Page et al, 2017) or stroke (Scholten et al, 2019) using the comprehensive COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines (Mokkink et al, 2018), but no studies have evaluated the psychometric properties among care partners within the spectrum of PD-MCI/PDD/DLB.…”
Section: Introductionmentioning
confidence: 99%
“…Both the MSIS-29 and FAMS scales are validated in MS and are recommended as outcome measures for MS by the American Physical Therapy Association EDGE MS Task Force 2011. 28 Although the other instruments have not been directly validated within the MS population, they are used within spinal cord injury, 26 , 29 , 30 , 31 brain injury, 32 and stroke populations, 33 as well as in other MS literature. 34 , 35 Given the functional similarities the participants may have shared with these other neurologic populations, the outcome measures were included to allow for easier comparison on effects across other studies in MS and other populations.…”
Section: Outcome Measuresmentioning
confidence: 99%